Automated measurement of plasma viscosity by capillary viscometer. Issue 11 (November 1988) - Cooke, B M; Stuart, J
Abstract : Plasma viscosity has several advantages over the erythrocyte sedimentation rate as a measurement of an acute phase response of more than 24 hours' duration. A new capillary viscometer (Coulter Viscometer II), which gives an automated measurement of plasma viscosity, was compared with the selected manual method (Harkness viscometer) of the International Committee for Standardization in Haematology. Automated measurement of plasma viscosity at 25 degrees C showed close correlation (r = 0.979, p less than 0.002) with the selected method for 160 specimens of plasma. Satisfactory precision both within batch and between batch (coefficients of variation of 1.7% or less) was obtained at viscosity values up to 5.7 mPa.s. There was no detectable carry over between samples and viscosity values were corrected adequately for ambient temperature for the range 15-32 degrees C. Careful daily cleaning was required to prevent accumulation of protein within the automatic sampling valve of the instrument. Automated measurement of plasma viscosity is an attractive alternative to measurement of the erythrocyte sedimentation rate.